2009
DOI: 10.1097/acm.0b013e31819fb7ff
|View full text |Cite
|
Sign up to set email alerts
|

The Conscientiousness Index: A Novel Tool to Explore Students’ Professionalism

Abstract: The results suggest that the CI measures a scalar objective trait that corresponds well with professional behavior as perceived by staff members in an undergraduate medical school. The individual decisions making up the CI are objective and easy to collect, making it a relatively simple and uncontroversial method for exploring students' professionalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 13 publications
2
71
1
Order By: Relevance
“…The 'Conscientiousness Index' (CI) was developed at Durham University, UK and consists of points awarded and deducted for a range of objective administrative measures, resulting in each student having a CI score at the end of the academic year. The CI scores showed a positive correlation with staff estimates of professionalism (6) and also with estimates of professionalism made by peers (7).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…The 'Conscientiousness Index' (CI) was developed at Durham University, UK and consists of points awarded and deducted for a range of objective administrative measures, resulting in each student having a CI score at the end of the academic year. The CI scores showed a positive correlation with staff estimates of professionalism (6) and also with estimates of professionalism made by peers (7).…”
mentioning
confidence: 83%
“…In line with the original study (6), all students started with a baseline 50 CCI points. This was done to avoid some students CCI scores being negative at the end of the year.…”
Section: Data Collectedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this a relatively untouched area in medicine selection, despite the pressing need for medical professionals to ''do more with less'', and the changing nature of many medical roles to require entrepreneurialism in the future (Gregory 2009). Patterson and Zibarras (2016) note that conscientiousness and innovation have been found to correlate negatively, which raises a challenging dilemma since previous research has consistently shown a positive association between conscientiousness and various indices of education and training success and job performance (McLachlan and Macnaughton 2009;Woods et al 2016;Barrick et al 2001). This study explores the use of a trait-based measure of creativity and innovation potential and evaluates its efficacy for use in selection for medical education; finding that different aspects of innovation are associated with different sub-facets of conscientiousness, and that motivation to change is the key significant predictor of creative problem solving, over and above personality traits.…”
Section: How Can We Best Select For Important Personal Attributes Andmentioning
confidence: 99%